THE IMPACT OF COLORECTAL CHROMENDOSCOPY WITH ENHANCED MUCOSAL IMAGING ON ADENOMA MISS RATE IN SCREENING COLONOSCOPY - LUZ,Bruna Suelen Raymundo (2021)
ABSTRACT BACKGROUND: Colonoscopy is the gold standard for the diagnosis and treatment of adenomas. It is related with decreased colorectal cancer incidence and mortality. However, an important problem is missed colorectal adenoma. All efforts should be undertaken to reduce this rate. Enhancing imaging technologies including electronic chromoendoscopy and magnification has been increasingly adopted for improving the colorectal neoplasia detection rate and the detailed study of its surface, as well. I-scan images (Pentax, Tokyo, Japan) provides virtual chromoendoscopy in real-time during the examination to view the surface pattern, highlighting the microvasculature of the neoplastic lesion. The evidence on the impact of the use of I-scan on the colorectal adenoma detection rate is scarce. OBJECTIVE: To evaluate whether the use of I-scan has impact on the adenoma miss rate (AMR) of screening colonoscopy exams. METHODS: Observational and prospective study conducted by monitoring patients over 50 years undergoing colonoscopy. There were two groups: Group 1 - first inspection with standard high-definition white-light (HDWL) followed by a second inspection with I-scan 1; Group 2 - first inspection with I-scan 1 followed by a second inspection with standard HDWL. The primary outcome was the AMR from the first exam, calculated with the number of adenomas detected in the second exam, divided by the total number of adenomas detected in both exams. RESULTS: A total of 85 patients participated in the study. 14 were excluded, with a final sample of 71 patients, in the Group 1, 34 patients, and the Group 2, 37. A total of 58 adenomas were detected, 40 in the first inspection (20 in each group) and 18 in the second inspection in group 1. The overall AMR was higher for the Group 1 than the Group 2 (47.4% vs 0% P=0.0002). CONCLUSION: The use of I-scan 1 during colonoscopy exam reduces the AMR.